ANALISIS PENERIMAAN PELANGGAN TERHADAP APLIKASI PLN MOBILE DENGAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Muhammad Zulifan Aditya (Universitas Katolik Musi Charitas, 2019)
This study conducted a study and looked at the level of acceptance of PLN Mobile Application users in the city of Palembang. The method used is the Technology Acceptance Model (TAM) method. The statistical test in this study uses the Statistical Package for the Social Sciences (SPSS) program. using the variables Perceived Usefulness, Perceived Ease of Use, Attitude Toward and Acceptance of IT. The sample in this study were the users of the PLN Mobile Application totaling 100 people by determining the number of samples using the Slovin formula and using simple random sampling techniques. The data obtained are tested by testing classic assumptions and research results show that Perceived Usefulness and Perceived Ease of Use partially or separately affect the attitude of users or Attitude Toward Using, Perceived Usefulness partially or separately affect the acceptance of the PLN Mobile Application and indirectly supported by user perceptions about the ease of use of the PLN Mobile Application or Perceived Ease of Use. This study also proves that the factor of user attitude or Attitude Toward does not affect the user's decision to accept the PLN Mobile Application.